Sudden cardiac death in young First Nations Australians in the Northern Territory, Australia: Potential implications for pre-participation screeningKey Points - Sonali Pande; Viran DeSilva; Elizabeth Paratz; Marianne Tiemensma; Nadarajah Kangaharan (JSAMS Plus, 2025)
Objective: To present data from coronial records on sudden cardiac death (SCD) cases seen in young, First Nations Australians in the Northern Territory of Australia, estimate its incidence, and propose potential pre-participation screening strategies. Design: Retrospective observational study. Methods: Coronial records of sudden cardiac death cases in First Nations Australians in the Northern Territory under 40 years of age occurring between 2019 and 2023 were reviewed to study the incidence, demographics, medical history, circumstances of death and causes of death with autopsy and toxicology analysis. Results: A total of 59 SCD cases in First Nations Australians under 40 years of age were recorded in the Northern Territory with an annual incidence of 19.8 cases per 100,000 persons. The mean ± SD of age was 32.8 ± 6.14 years. There were 61 % male and 2/3 of SCD cases occurred in remote location. Coronary heart disease (n = 36; 61 %) was the most common cause of death. In 3 cases, SCD was related to sports or exercise activity. Most common medical co-morbidities were cardiac (38.9 %), Diabetes mellitus (35.6 %), and rheumatic heart disease (20.3 %). Smoking (37.3 %) and alcohol abuse (32.2 %) were the most common risk factors. Conclusions: SCD is more common and coronary heart disease and rheumatic heart disease are the most common causes in First Nations Australians in the Northern Territory under the age of 40 years. Medical co-morbidities and risk factors are prevalent in this population. There is a need for First Nation Australians specific local guidelines for a comprehensive pre-participation Heart-Health assessment.